Paracapsulapagurus poponguinensis, a new hermit crab (Decapoda, Anomura, Paguroidea) from the Maastrichtian of Senegal. (19th October 2016) - Hyžný, Matúš; Fraaije, René H.B.; Martin, Jeremy E.; Perrier, Vincent; Sarr, Raphaël
Abstract: Based on a single right cheliped from the Cape de Naze Formation (middle–upper Maastrichtian), Senegal, a new genus and species of hermit crab with capsulated setae is described. Paracapsulapagurus poponguinensis n. gen. n. sp. is characterized by platy, scale-like, non-spinose tubercles with setae arranged in curved rows. This is only the third record of a fossil hermit crab with capsulated setae. These are documented in detail using SEM-imaging. For the first time, capsulated setae are also figured for the Early Jurassic hermit crab Schobertella .